Strengthening Islamic Law in Building Justice and Social Welfare - Katterbauer (Edujavare Publishing, 2025)
This study analyzes the role of Islamic law in strengthening justice and social welfare in contemporary society. The research aims to examine how Islamic legal principles are applied in social and economic life and how they contribute to the realization of justice and welfare. A normative legal research method is used with conceptual and doctrinal approaches, based on secondary data from Islamic legal texts, academic literature, and institutional reports. The findings indicate that Islamic law promotes justice through the principle of ʿadl and enhances social welfare through mechanisms such as zakat, waqf, and other social finance instruments. However, challenges such as interpretative differences and globalization pressures affect its implementation. The study concludes that Islamic law remains a vital framework for promoting justice and social welfare when applied consistently within a structured legal system.